Compliance with the Environmental Regulations of FDI Establishments in the Automotive and Auto Parts Industry in Mexico - Gonzales Acolt, Roberto (2025)
The objective of this study was to analyze the degree of compliance with environmental regulations in Mexico by establishments in the transportation equipment manufacturing subsector (automotive and auto parts) that have Foreign Direct Investment (FDI) participation in their share capital. To test this relationship, a logit model was used, where the dependent variable took the value 1 if the productive unit of this subsector complied with at least one environmental regulation, and 0 otherwise; the central explanatory variable was whether the economic unit of the automotive and auto parts industry with FDI, and other independent control variables were added. The results show that establishments in this industry with FDI are more likely to comply with environmental regulations. Likewise, establishments within the subsector that are classified as large enterprises, organized into corporate groups, and located in the central-western region exhibit a higher likelihood of complying with environmental regulations. Furthermore, the establishments in this industry that carry out other practices to improve and care for the environment are more likely to implement environmental standards. The main result of the study supports the halo hypothesis, as a positive and significant effect was found regarding compliance with environmental regulations by of the transport equipment manufacturing establishments with FDI.